EFFICACY OF A MINDFULNESS-BASED COGNITIVE THERAPY (MBCT) INTERVENTION FOR TEST ANXIETY IN PRIMARY SCHOOL STUDENTS - Yassine Belhassen; Hana Ben Romdhane; Amine Ali (International Journal of Educatio Elementaria and Psychologia, 2026)
Test anxiety is a common challenge among primary school students, often impacting their academic performance and well-being. Mindfulness-Based Cognitive Therapy (MBCT) has shown promise in managing anxiety-related disorders, but its efficacy in reducing test anxiety in primary school students remains underexplored. This study aims to evaluate the effectiveness of an MBCT intervention in reducing test anxiety among primary school students and improving their academic performance. A randomized controlled trial design was used, with 60 students assigned to either the MBCT intervention group or a control group. The MBCT program consisted of 8 weekly sessions, focusing on mindfulness practices, cognitive restructuring, and stress reduction techniques. Pre- and post-intervention assessments were conducted using the Test Anxiety Inventory (TAI) and academic performance records. The results showed a significant reduction in test anxiety scores for the intervention group compared to the control group (p < 0.05). Additionally, students in the MBCT group demonstrated improved academic performance, particularly in subjects where test anxiety had previously hindered their progress. These findings suggest that MBCT is an effective intervention for managing test anxiety in primary school students, contributing to both emotional well-being and academic success. Future studies should explore the long-term impact of MBCT and its applicability to other student populations.